Adenomatoid odontogenic tumor, an uncommon tumor - K Vasudevan; Senthil Kumar; Vijayasamundeeswari; Srivel Vigneswari (Wolters Kluwer Medknow Publications, 2012)
Here we report a case of adenomatoid odontogenic tumor (AOT) in the maxilla in a young girl aged 14 years and its surgical management. We also review the literature and variations in the nomenclature and classifications of this interesting tumor. The review of literature gives an interesting picture regarding terminologies in the past and dilemma in classifying this tumor. The introduction of the name adenomatoid odontogenic tumour has resulted in the simpler and fruitful surgical management like enucleation and curettage with no reports of recurrences. In the past, similar lesion with the terminology like adeno ameloblastoma has resulted in unnecessary mutilating surgery. The conflicting views whether the lesion is being neoplasm or an anomalous hamartomatous growth is also being discussed.